When dystrophia meets ischaemia: a case report on cardiac involvement of myotonic dystrophy type 2 and successful arrhythmia elimination after catheter ablation. Issue 2 (14th February 2022) - Guckel, Denise; Farr, Martin; Sommer, Philipp; Sohns, Christian
Abstract: Background: This case reviews the cardiac involvement of myotonic dystrophy type 2 in terms of ventricular arrhythmias (VAs) and individual myocardial scar formation as target for catheter ablation. Case summary: A 62-year-old woman with myotonic dystrophy type 2 and a severely reduced left ventricular ejection fraction (25%) presented with recurrent episodes of VAs and consecutive implantable cardioverter-defibrillator therapies. The patient already underwent two VA ablation attempts focusing on an ischaemia-related arrhythmia substrate in the left ventricle. The patient was scheduled for repeat ablation after the progression of coronary artery disease was ruled out. Interestingly bipolar voltage as well as activation mapping revealed an arrhythmia substrate along with the basal and inferior aspects of the right ventricle (RV). Catheter ablation of this scarred area in the RV resulted in specific termination of the VAs. Due to end-stage heart failure, key heart transplant criteria were met. The patient was evaluated for heart transplantation and added to the waiting list. Hitherto, no further VAs were documented during follow-up. Discussion: As these patients present with specific dystrophia-related arrhythmia substrates, we propose pre-procedural visualization of dystrophy-associated arrhythmia substrates using cardiac magnetic resonance imaging allowing for personalized ablation approaches in these patients.